Digital Marketing, Market Place PELATIHAN PENGGUNAAN MARKET PLACE BERBASIS DIGITAL MARKETING BAGI PEKAKU UMKM TELUR ASIN DI DESA TALOK SARI KECAMATAN BUMIAYU - Agung Prayogi; Riska Sevia; Akmal Failasuf Latif (Kanigara, 2023)
This study aims to carry out training on the use of digital marketing-based market places for Micro, Small and Medium Enterprises (MSMEs) engaged in the production and sale of salted eggs in Talok Sari Village, Bumiayu District. The aim of this training is to increase the understanding and skills of MSME actors in utilizing the market place platform to expand market reach and increase the competitiveness of their businesses. This research will use a participatory approach method, in which researchers will work with the village government and the local MSME community to design a training program that suits the needs of salted egg MSME actors. The training will include an introduction to digital marketing concepts, an understanding of the market place, effective online marketing strategies, and the use of social media as a product promotion tool. The Expected outcome of this training is an increase in the knowledge and skills of MSME players in utilizing the market place platform to increase market access, attract new consumers, and increase sales of salted egg products. With this training, it is hoped that MSME actors can expand their business network through the effective use of digital technology. In conclusion, training on the use of digital marketing-based market places for salted egg MSMEs in Talok Sari Village is an important step to improve their ability to utilize digital technology for product marketing.